A Comparative Study of Teaching Process of Presenting Product Sketch Design of Industrial Design Program - Pracha Pijukkana; Yanin Rugwongwan (My University, 2017)
This research studies the teaching process of idea communication for industrial product design sketching. The objective of this research is to make a comparative study on the efficiency of two teaching processes between teaching with detailed information and teaching with conceptual frameworks for groups of students who have different learning aptitudes; which are an aptitude in theoretical subjects or an aptitude in practical subjects. The study also included differences in learning styles of the industrial design program undergraduate students. The researchers came up with an experiment of creating sketch design ideas for a product in which the researchers classified the students’ learning processes from curriculum subjects and academic achievements. The results found that curriculum subjects and students’ learning aptitude can be grouped into two major groups: students who have accumulated scores in theoretical subjects and students who have accumulated scores in practical subjects. These two groups of students have different aptitudes in sketch design idea communication processes: a process of sketching with given detailed information and a process of sketching with given conceptual framework. Although these are different processes, the teaching and learning of these two product design processes have the same objectives: to create design ideas and to support design creativity by using the concept of interaction between the brain, hands and shapes that appear on paper to present the sketch product and to guide the teaching and learning of industrial product design, suitable for students who have different characteristics and help increase their academic achievements.
Keywords: Sketch; Aptitude; Industrial design; Design Education and Practice